초기 스타트업의 부트스트래핑 사례: ㈜블랙루비 스튜디오 - 원치운(Chi-Woon Won); 배태준(Tae-Jun Bae) (벤처창업연구, 2019)
The purpose of this study is to explain the bootstrapping method to understand the process of overcoming the difficulties experienced by the limited resources of the initial start-up, through the example of Black Ruby Studio. Most nascent start-ups have constrained resources. This problem is a subject that is constantly being repeated in entrepreneurship research. Despite these problems, there are relatively few studies detailing the process of overcoming the initial difficulties of start-up. Bootstrapping is described as a way to reduce external inflows, reduce risk, and resolve funding issues internally. Many start-ups initially rely on bootstrapping as a way to solving scarce funds and limited resources. Therefore, this study reviewed the prior literatures in bootstrapping, and used 32 detailed item bootstrapping methods suggested in Winborg & Landstrom(2001) on bootstrapping in order to understand bootstrapping concept of start-up. This study gives insightful implication to prospective founders by using the bootstrapping method for survival of start-up and the process of overcoming the difficulties in the start-up. 본 연구는 초기 스타트업의 제한된 자원으로 겪게 되는 어려움을 극복하는 과정을 이해하기 위해 부트스트래핑(bootstrapping)방법을 적용하여, 한양대학교 학생창업 기업인 (주)블랙루비 스튜디오의 사례를 통해 설명하고자 하였다. 스타트업 초기 겪게 되는 자원 조달에 대한 문제는 끊임없이 반복되어 오고 있는 연구 주제이다. 이와 같은 문제에도 불구하고 창업 관련 연구 분야에서 스타트업의 초기 어려움을 극복하는 과정을 자세히 설명하는 연구들은 비교적 많지 않다. 스타트업들은 창업을 시작할 때, 부족한 자금과 제한된 자원을 해결하기 위한 방법으로 외부의 자금 유입을 줄여 위험을 감소시키고 내부적으로 자금 문제를 해결하는 방법인 부트스트래핑에 의존하게 된다. 따라서, 본 연구에서는 스타트업의 부트스트래핑 개념을 이해하기 위해 관련된 선행연구 검토와 부트스트래핑에 관한 Winborg & Landstrom(2001)의 연구에서 제시된 32개의 세부적인 항목별 부트스트래핑 방법을 바탕으로 블랙루비 스튜디오의 창업자인 소재우 대표와의 수 차례의 심층 인터뷰를 통해 스타트업의 생존을 위한 부트스트래핑 방법 활용과 창업 초기 어려움을 극복하는 과정을 면밀히 분석하여 예비창업자들에게 통찰력 있는 시사점을 전한다.